A Review of Applications of Nanofibers Fabrication via Electrospinning and Non-Electrospinning Techniques - Ramadhan, Roaa; Ahmed J.M.AL-Zuhairi; Ahmad S. Lateef; Mohammed K. Khalaf; Amer D. Majeede (Indonesian Journal of Material Research, 2026)
Nanofibers possess distinct traits and adaptable possible uses that can help with both creative approaches and chances for sustainable production of energy, as well as providing innovative solutions to the complicated problems of the biomedical, medicinal, and environmental surrounded. It describes the development and timelines of nanofiber technologies with different physical and chemical properties. It also discusses the different methods of production, including traditional methods of spinning and other non-electrospinning methods, like needleless spinning. Specifically, advanced nanofibers are employed as electrodes and membranes in solar cells, batteries, fuel cells, and supercapacitors. They are also utilized in low pressure procedures for the treatment and purification of blood, water, and wastewater, as well as membrane technologies for ultra-high efficiency air filtration systems.